Rootstock influence on the performance of field-grown grapevines (Vitis vinifera) during autumn-winter harvest - FRANCISCO CAMARA; Cláudia Rita de Souza; Renata Vieira da Mota; Naíssa Prévide Bernardo; Laura Franco Carvalho Lucas; Fernanda de Paula Fernandes; Lucas Bueno do Amaral; Isabela Peregrino (OENO One)
The production of high-quality wines elaborated from grapes harvested during the dry winter has considerably increased in the Brazilian southeast, mainly with the Syrah cultivar. However, the double pruning management used to induce winter harvest has reduced the vigour and yield of some classic cultivars such as Merlot and Cabernet-Sauvignon. In viticulture, rootstocks became a useful tool to manipulate vegetative and reproductive vigour. This study aimed to determine the effect of eight rootstocks on vigour, yield and grape quality of Merlot, Cabernet-Sauvignon, and Syrah grapevines grown during the autumn-winter season in the south of Minas Gerais under double pruning management. The treatments were evaluated from 2018 to 2022 seasons, in a 3 × 8 factorial arrangement, with three cultivars and eight rootstocks. The yield and grape quality of Syrah, Cabernet-Sauvignon, and Merlot grapevines under double pruning management could be improved using medium to high vigorous rootstocks. To all cultivars, the combination with IAC 766, SO4, RUPESTRIS, GRAVESAC, 101-14, and KOBER increased yield with no impairment in grape maturation. IAC 572 can be used under double-pruning management for Merlot and Cabernet-Sauvignon when long spur pruned. However, grafting must be carefully recommended, because this rootstock is extremely vigorous and can affect the balance between vegetative and reproductive vigour.